Rekonstruksi Budaya Hukum Nasional yang Berbasis Nilai-nilai Budaya Hukum Bangsa Indonesia - Toto Tohir (Syiar Hukum, 2011)
Indonesia is former Dutch colony in which its legal system is heavily influenced by the Continental European Legal System. Geographically located in the continent of  Europe which was colonized by France, Holland has traditionally followed the Continental European Legal System. This System is formally and substantially adopted by Indonesia. The Continental European Legal System is based on a system of law that has been created by Parliament. Conversely, cultural-customs differences among the Indonesian communities have led to the conflict between the existing law and  law cultural. It is therefore that effort is urgently needed to adjust both the system and reconstruction of the law faculty curriculum in order to accommodate the clash between one law cultural and another one.